2021
DOI: 10.3390/w13020188
|View full text |Cite
|
Sign up to set email alerts
|

Riparian Vegetation Structure Influences Terrestrial Invertebrate Communities in an Agricultural Landscape

Abstract: Stream and terrestrial ecosystems are intimately connected by riparian zones that support high biodiversity but are also vulnerable to human impacts. Landscape disturbances, overgrazing, and diffuse pollution of agrochemicals threaten riparian biodiversity and the delivery of ecosystem services in agricultural landscapes. We assessed how terrestrial invertebrate communities respond to changes in riparian vegetation in Romanian agricultural catchments, with a focus on the role of forested riparian buffers. Ripa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 106 publications
1
15
0
Order By: Relevance
“…We observed more chironomid midges at unbuffered reaches which are weak fliers and their dispersal has been shown to be restricted to the stream edges [74]. Therefore, higher abundances with active aerial dispersing taxa at the buffered reaches in our study indicate the potential for the reciprocal transfer of subsidies to terrestrial ecosystems [5,47,[75][76][77].…”
Section: Implications For Cross-ecosystem Connectivitysupporting
confidence: 47%
“…We observed more chironomid midges at unbuffered reaches which are weak fliers and their dispersal has been shown to be restricted to the stream edges [74]. Therefore, higher abundances with active aerial dispersing taxa at the buffered reaches in our study indicate the potential for the reciprocal transfer of subsidies to terrestrial ecosystems [5,47,[75][76][77].…”
Section: Implications For Cross-ecosystem Connectivitysupporting
confidence: 47%
“…Riparian zones are important habitats for potential pests and natural enemies that affect agriculture [ 93 ]. All three surveyed sites were near rice fields; hence, they can become habitats for potential agricultural pests.…”
Section: Discussionmentioning
confidence: 99%
“…While species richness can provide a broad-scale view into the assembly of ecological communities, understanding influences on community composition can provide critical deeper insights into life history and dispersal characteristics that could affect establishment across the landscape [115][116]. Parallel to richness, we found that landscape connectivity, SLA, and stream identity drove differences in community structures between individual willow trees.…”
Section: Discussionmentioning
confidence: 72%